Haemato-biochemical profiles, body condition and FAMACHA scores at various ages and their interrelations in Surti goats - SORATHIYA, LALITCHANDRA AMNJIBHI; FULSOUNDAR, A.B (Indian Journal of Animal Production and Management, 2017)
The effect of age on haemato-biochemical parameters, BCS and FAMACHA scoring were studied in traditionally reared Surti goats in south Gujarat. Total 240 adult goats, 72 yearlings (1 year to 1st kidding) and 48 kids (Upto 6 month age) were selected for study. All were monitored for FAMACHA and BCS simultaneously with blood samples collection. The PCV was measured by micro-haematocrit method and biochemical parameters were measured on biochemical analyzer. BCS and PCV were significantly higher in kids and yearlings than adult goats. The younger goats were also having low FAMACHA scoring. Blood glucose, cholesterol, total protein, albumin, A:G ratio, urea, creatinine, calcium, magnesium, ALT and AST did not vary significantly between kids, yearlings or adults Surti goats, whereas, triglycerides and phosphorus were found significantly higher in younger goats and globulin was significantly higher in adult goats. BCS and PCV have significantly positive whereas FAMACHA has significant negative correlations with most of blood parameters.